The Relationship Of Reproductive Health And Personal Hygiene Behavior On The Incidence Of Vucility In Ziadatul Irfan Tarumajaya Junior High School Students, Bekasi, 2025 - Indah Yuliani; Hasipah Nurseha (Jurnal Ners, 2026)
Background: Reproductive health is a state of complete physical, mental, and social well-being, not merely the absence of disease or infirmity, in all matters relating to the reproductive system and its functions and processes. According to the WHO (2023), the prevalence of reproductive organ diseases in women includes bacterial vaginosis at 23-29%, trichomoniasis at 156 million women worldwide, chlamydia infections at 128.5 million, and 500 million women experiencing sexually transmitted infections characterized by vaginal discharge. A person's knowledge of personal hygiene also influences their behavior in maintaining and caring for their reproductive health. Health education about reproductive health is important for adolescents so they have the correct information and knowledge about reproductive health. Research Objective: To determine the relationship between reproductive health knowledge and personal hygiene with the incidence of vaginal discharge in female students at SMP Ziadatul Irfan Tarumajaya Bekasi in 2025.Research Method: This research method uses a descriptive analytical approach with a cross-sectional method. Using the Chi-square test, the data collection involves independent variables (risk) and dependent variables (risk) carried out at the same time.Research Results: Statistical tests using the Chi-Square test showed that respondents with a P-value of 0.05 < 0.005 for reproductive health behaviors indicated a significant relationship between reproductive health knowledge and vaginal discharge. Furthermore, for personal hygiene behaviors, the P-value was 0.375 > 0.05, indicating no significant relationship between personal hygiene behaviors and vaginal discharge.Conclusions and Recommendations: As input or reference for further research on Reproductive Health and Personal Hygiene Behaviors on Vaginal Discharge. Overall, reproductive health knowledge and personal hygiene behaviors play an important role in preventing vaginal discharge. Therefore, efforts to improve reproductive health education accompanied by the implementation of good personal hygiene are essential as preventative measures.